2004
DOI: 10.1002/ana.20161
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐β stabilizes barrier characteristics of brain endothelial cells in vitro

Abstract: Multiple sclerosis (MS) is accompanied by a breakdown of the blood-brain barrier (BBB) leading to edema formation and aggravation of the disease. Interferon-beta (IFN-beta) has been approved for the treatment of MS and besides its immunomodulatory effects has been demonstrated to lead to a stabilization of BBB integrity in vivo. To investigate whether human recombinant IFN-beta exerts direct effects on the BBB, we used an in vitro BBB model in which brain endothelial cells in coculture with astrocytes form a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
83
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 49 publications
6
83
0
Order By: Relevance
“…Adenosine is a known anti-inflammatory agent, which promotes endothelial integrity and has neuroprotective properties [17,[22][23][24]. IFN-b directly or indirectly stabilizes the BBB in RRMS patients, as suggested by a number of in vitro studies [25,26]. Moreover, gadolinium enhancement of magnetic resonance imagins lesions is indicative of BBB damage, and treating MSpatients with IFN-b in vivo leads to an early reduction in the appearance of gadolinium-enhancing lesions [2,8].…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine is a known anti-inflammatory agent, which promotes endothelial integrity and has neuroprotective properties [17,[22][23][24]. IFN-b directly or indirectly stabilizes the BBB in RRMS patients, as suggested by a number of in vitro studies [25,26]. Moreover, gadolinium enhancement of magnetic resonance imagins lesions is indicative of BBB damage, and treating MSpatients with IFN-b in vivo leads to an early reduction in the appearance of gadolinium-enhancing lesions [2,8].…”
Section: Discussionmentioning
confidence: 99%
“…7,36,[56][57][58][59][60] Consequently, IFN-b is thought to exert part of its beneficial effect by limiting the transmigration of activated pro-inflammatory T cells across the blood-brain barrier into the CNS. 61,62 Another possible mechanism underlying the therapeutic effect of IFN-b is the inhibition of CD4 + and CD8 + T-cell activation and proliferation. [8][9][10] Based on the difficulties they had in establishing MOG-reactive T-cell clones from IFN-b-treated MS patients, Koehler et al concluded that therapy with IFN-b might reduce the number of antigenspecific CD4 + T cells in the periphery.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 BBB damage commonly associated to inflammatory events has been reported in several central nervous system (CNS) infections and neurodegenerative diseases. [3][4][5] Although BBB permeability disturbances seem to be critical steps as they lead to brain damage, neither the cause of these phenomena nor the effective participation of BBB in such diseases are established.The cerebral vascular wall was formally considered as a barrier that isolates brain from immunecontrol. However, the presence of immune cells in the brain parenchyma in healthy animals, and their increased cerebral residence in pathogenic conditions, demonstrate that the recruitment of inflammatory cells into the CNS, through the BBB, takes place.…”
mentioning
confidence: 99%
“…1,2 BBB damage commonly associated to inflammatory events has been reported in several central nervous system (CNS) infections and neurodegenerative diseases. [3][4][5] Although BBB permeability disturbances seem to be critical steps as they lead to brain damage, neither the cause of these phenomena nor the effective participation of BBB in such diseases are established.…”
mentioning
confidence: 99%